2018
DOI: 10.1007/s00068-018-0996-6
|View full text |Cite
|
Sign up to set email alerts
|

Burn first aid knowledge and its determinants among general population of Rawalpindi

Abstract: A significant limitation of knowledge regarding BFAT was seen among the general population of Rawalpindi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 18 publications
4
22
1
2
Order By: Relevance
“…Another study conducted in the United Kingdom reflected subpar knowledge of BFAT amongst healthcare workers [9]. The situation in Pakistan also follows this global streak, since our results were comparable with other studies conducted in Pakistan in terms of inadequate knowledge regarding BFAT [13][14].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Another study conducted in the United Kingdom reflected subpar knowledge of BFAT amongst healthcare workers [9]. The situation in Pakistan also follows this global streak, since our results were comparable with other studies conducted in Pakistan in terms of inadequate knowledge regarding BFAT [13][14].…”
Section: Discussionsupporting
confidence: 85%
“…Beliefs like puncturing them and application of toothpaste were common and need to be addressed in the future to get rid of common misconceptions, because such actions may exacerbate the initial injury. Contrary to the study of Mishra et al, where a majority of the participants (82.3%) knew the correct answer of removing jewelry and accessories from the burnt area, students in our survey responded poorly [13,16]. Less than half of medical students marked the right answer which is alarming and needs to be addressed since accessories not only get in the way of injury, but the following edema makes the future removal difficult and painful.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Treatments reported included 81.8% having applied water to the injured area, 72.3% having removed clothing or accessories from the area of injury, and 71 (51.8%) using ice to cool the injured area. Another study from Pakistan in Rawalpindi showed that toothpaste (47.5%) followed by cool running water (20.3%) were the two most frequently applied items following a burn injury [ 16 ], while in Nigeria, water lavage was used in 49 (29.2%) cases, raw eggs in 21 (12.5%), pap in 16 (9.5%) [ 17 ]. Similar to our findings, another study conducted in Saudi Arabia by Almutlaq et al 2020 [ 5 ] reported that most respondents used cold water or honey as post-burn therapy.…”
Section: Discussionmentioning
confidence: 99%